The effect of the frequency of prescribed burning on annual soil carbon balance in a loblolly-shortleaf pine forest in East Texas - Ono, Moeka; Noormets, Asko; Mitchell, Sarah (Frontiers in Forests and Global Change, 2025)
Prescribed burning is a common forest management tool, and is expected to affect soil carbon (C) content and dynamics, yet data on this remain limited. Here we report the effect of prescribed burning frequency on net soil C balance in three loblolly-shortleaf pine stands that have undergone different fire regimes over the past 20 years: low-intensity ground fires applied (i) annually, (ii) intermittently (every 2–4 years), or (iii) not at all. Prior to the initiation of differential burn frequencies in 2001, all stands underwent minimal management. Differences in soil C pools and fluxes were attributed to burn frequency treatments. Frequent burns reduced fine root biomass and thus soil autotrophic respiration (Ra). Indirectly, lower fine root detritus production also resulted in reduced heterotrophic respiration (Rh). Fine root productivity and mortality, however, were similar across burn frequencies, resulting in faster fine root turnover with burning. Conversely, the no-burn stand had the highest fine root biomass (BFR) and the highest Ra: BFR ratio (although statistically non-significant), suggesting higher investment in the maintenance of fine roots. Combined with the highest total belowground C flux, and highest soil CO2 efflux, especially from Ra, but also from Rh, the results suggest greater metabolic activity belowground in the no-burn than burned treatments, possibly due to greater mycorrhizal colonization. As a result of these mutually offsetting responses, the net soil C balance did not significantly differ by burn frequency, ranging from −71 ± 123 to −167 ± 104 g C m−2 year−1.